Hubungan Tingkat Pengetahuan Tentang Perilaku Mencuci Tangan dan Penggunaan Alat Pelindung Diri dengan Penerapannya pada Terapis Gigi dan Mulut di RSKGM Kota Bandung - Hoerunisa, Siti Nisa; Mulyanti, Sri; Fatimah, Siti; Widyastuti, Tri (Poltekkes Kemenkes Bandung, 2024)
The high incidence of disease transmission in hospitals is an indicator of the importance of control or prevention efforts by implementing precautionary standards. In increasing efforts to prevent disease transmission, nurses need knowledge and attitudes in using personal protective equipment (PPE) to avoid the risk of disease transmission from patients to nurses and fellow patients. The aim of this research is to determine the relationship between the level of knowledge about hand washing behavior and the use of personal protective equipment and its application to dental and oral therapists at RSKGM Bandung City. This research method uses quantitative with a cross-sectional design. The research results show that washing hands must be done properly before and after carrying out care procedures even if wearing gloves or other protective equipment to eliminate or reduce microorganisms on the hands so that the spread of disease can be reduced and the environment is protected from infection. It can be concluded that from the results of the Kendal tau'b statistical test with a p value of 0.000, it shows that there is a relationship between the knowledge of dental and oral therapists and the implementation of cross-infection control at RSKGM Bandung City.